What Does Evaluation Look Like in a Trust-Based Context? (Trust-Based Philanthropy Project, 2023)
The fifth session of the Demystifying Trust-Based Philanthropy webinar series took place on Wednesday, July 12th 2023. There is a mispercept ion that trust-based philanthropy is at odds with rigorous impact eval uation because of its focus on relationships over project-specific met rics. Trust-based evaluation is indeed rigorous, but it differs from t he sector standard in that it prioritizes a learning stance over a pro ving stance. This ultimately helps illuminate a more nuanced understan ding of the barriers and catalyzers of social change, as well as usefu l information that can help grantmakers improve their strategies towar d advancing impact. This session unpacked these important nuances and highlighted examples of how grantmakers are relying on rigor and conti nuous learning to understand impact. Special thanks to our speakers fo r this session: Brenda Solorzano, CEO, Headwaters Foundation Sarah Wal czyk, Executive Director, Satterberg Foundation Shari Turitz, Vice Pre sident for Programs, American Jewish World Service Gratitude to our ph ilanthropic-serving organization partners for bringing this session an d discussion space to their grantmaker members. Learn more about the T rust-Based Philanthropy Project: Website: https://www.trustbasedphilan thropy.org/ Follow us on Twitter:   / trustbasedphil   Follow us on Li nkedIn:   / trust-based-philanthropy